1969
DOI: 10.12669/pjms.305.5239
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors Affecting Quality of Life of Hemodialysis Patients-Lahore,pskistan.

Abstract: Objective: The objective of the study was to determine the demographic factors affecting Quality Of Life (QOL) of hemodialysis (HD) patients. Methods: This observational study was conducted at Shalamar Hospital, Lahore. Patients of End Stage Renal Disease (ESRD) and on maintenance HD for more than three months were included during the period March to June 2012. Patient of ESRD not on dialysis and Acute Renal Failure were excluded. One hundred and twenty five patients who fulfilled the criteria were included. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 0 publications
10
40
1
1
Order By: Relevance
“…The association of age with HRQOL is quite complex and illustrates the complexity of the QOL concept [4] that age was strongly inversely associated with the physical domain scores. As age increases in the elderly, physical function of the body decreases [2,4,14,[18][19][20][21][22]. A recent Saudi showed that age was a negative predictor of HRQOL score [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of age with HRQOL is quite complex and illustrates the complexity of the QOL concept [4] that age was strongly inversely associated with the physical domain scores. As age increases in the elderly, physical function of the body decreases [2,4,14,[18][19][20][21][22]. A recent Saudi showed that age was a negative predictor of HRQOL score [2].…”
Section: Discussionmentioning
confidence: 99%
“…The potential to increase the number of dialysis patients who are employed exists if the barriers to employment that have been identified can be removed [26]. Patients who are satisfied with hemodialysis treatment and accepting it have better working capacity [22]. Directing rehabilitation efforts toward the population of dialysis patients who identify themselves as willing and able to work seems a worthwhile strategy to improve their QOL [26].…”
Section: Discussionmentioning
confidence: 99%
“…WHOQOL-BREF questionnaire has been validated for assessing QOL in patients with CKD in different settings 14 and has been used to assess QOL by a number of studies elsewhere. 3,4,19 We used sociodemographic data as predictor variables and all four domains, including items 1 and 2, as outcome variables. 20 Results of descriptive analysis are presented as mean±SD.…”
Section: Methodsmentioning
confidence: 99%
“…According to Muhammad anees [3] negative predictor of quality of life in psychological domain. Monthly income is positive predictor of quality of life factor affect more.…”
Section: Related To Association Between Demographic Variable and Factmentioning
confidence: 99%
“…Education level is a positive factor for improving QOL of HD patients. [3] Study conducted by M.Shinde found that about 97% patients undergoing hemodialysis had severe stress In that 50% of patients undergoing hemodialysis always adopt emotion focused and problem orientation as their coping strategies, while 90% of patient sometimes used avoidance oriented coping strategy, while the others 56% sometime use the coping strategy of seeking support and isolated thoughts. The overall assessment reveals that though the subjects at undergo severe stress of the procedure they undergo.…”
Section: Introductionmentioning
confidence: 99%